Structural properties, genomic distribution of laccases from Streptomyces and their potential applications. (July 2022) - Kaur, Randhir; Salwan, Richa; Sharma, Vivek
Abstract: Microbial laccases also known as blue copper-containing oxidases, possess ability to perform under extreme conditions such as high temperature, broad pH and resistance to inhibitors such as sodium azide and sodium fluoride. Due to these characteristics, laccases of microbial origin are explored in industrial sectors for the treatment of effluents in textile industries, lignin degradation in biofuels, dye degradation, bioprinting and several other applications. The genus Streptomyces with filamentous morphology and high G+C content in their genome is a powerhouse of secondary metabolites and various enzymes of commercial interest. Despite their low redox potential, the ability of small laccases from Streptomyces to work under wide range of pH, substrate specificity and unusual resistance to inhibitors opens up new opportunities for their commercial applications. However, exclusive reviews on laccases of Streptomyces are not available in the literature. Structurally, the laccases from Streptomyces origin are small in size and consist of only two domains with homotrimeric organisation. At genomic level, the genes for multicopper oxidase and multicopper polyphenol oxidase also known as laccase like polyphenol oxidase are present in the genome of Streptomyces . Keeping in view the advantages of laccases from Streptomyces, an attempt has been made to understand the genomic distribution, complex homotrimeric structural organisation, genetic manipulations to engineer laccases with high redox potential has been discussed which can be used for several commercial applications. Highlights: The review article highlights laccases from Streptomyces and their importance. The structural insight on laccases from Streptomyces has been studied. The genomic distribution of laccase has been explored in the genus Streptomyces .